Studi Perencanaan Angkutan Umum dalam Kampus (Studi Kasus: Universitas Brawijaya) - Djahamouw, Putri Dwi Kinanti; Kore, Desri M. Hale (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The study aims to design an effective and sustainable public transportation system at Universitas Brawijaya, with the goal of creating a comfortable and efficient campus environment. In this research, factors such as user needs, the physical and social characteristics of the campus area, and sustainable transportation principles are thoroughly considered. The methodology used is a descriptive quantitative approach, with the field data collected through observations, questionnaires, and transportation model. This study is expected to address internal mobility issues, support the development of an environmentally friendly campus, and serve as a foundation for better transportation policies and planning in the future. The finding indicates that the internal movement patterns of campus residents, including students, faculty, and academic staff, tend to follow a one-way route, moving from the campus entrance to their activity locations and then returning. Movement between different activity locations, such as between faculties, rarely occurs. The movement survey generated a desire line, which led to the proposal of three alternative routes that can serve all user demand zones within UB campus area. Based on the calculations, 28 vehicles with a capacity of 14 passengers per vehicle are required during peak hours to serve all campus routes. The proposed routes cover the entire campus area, with maximum walking distance of 200 meters, ensuring that campus resident do not need to walk more than 200 meters to reach the public transport shelters